Upaya PT Pos Indonesia Dalam Melakukan Inovasi Layanan Di Era Revolusi Industri 4.0 - Amalia Munajah Nasution; Nuri Aslami (ManBiz: Journal of Management and Business, 2022)
This study aims to describe the changes that occurred in PT Pos Indonesia in the era of the industrial revolution 4.0. Along with the development of the era in the era of the industrial revolution 4.0, an era where technology takes on the role of almost all activities of human life. This study used descriptive qualitative method. For this reason, PT Pos Indonesia launched a new service to consumers, namely the Pospay service. The data collection technique is through literature study. The results of the research are the strategies/efforts used to face obstacles as well as rejection and follow the developments of the era of the industrial revolution 4.0 by innovating digital transformation which with one application can be used for convenience in various activities. Keywords: Change, Rejection, Innovation